Collaboration with the Disaster Resilient Village Forum in Disaster Emergency Response Simulation in Ngelang Kartoharjo Village Magetan. - Sunarto, Sunarto; Heru Santoso Wahito Nugroho; Suparji; Nani Surtinah; Verlingga Diah Oktiasa Putri; Sausan Hanifah Setyowati (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2024)
The problem faced by the Disaster Resilient Village Forum (Destana) in Ngelang Village, Kartoharjo District, Magetan is the difficulty in realizing community-based disaster preparedness, especially simulations of disaster emergency response. This community service activity is a follow-up to the results of research on priority parameters for realizing disaster preparedness using the Quadrant of Difficulty and Usefulness Preparedness method. The activity aims to improve the capabilities and skills of the Destana Forum in organizing disaster emergency response simulations, as well as building community resilience in facing disaster threats. The activity method is Participatory Action Research, which is applied through training and field practice. Participants were the administrators of the Destana Forum, elements of the Village Development Officer (Babinsa), Bhayangkara elements of Community Security and Order (Bhabinkamtibmas), and the community, with a total of 112 people. Activities were carried out on May 13 to May 17, 2024, in Ngelang Village, Kartoharjo District, Magetan. The results of the activity showed that the participants had succeeded in compiling and providing contingency plan documents, compiling threat scenarios, impact scenarios, and disaster event scenarios, as well as preparing operational rehearsal plans, conducting room rehearsals, and ending with a practical field rehearsal for disaster emergency response simulations. The conclusion from this activity is that strengthening community-based disaster preparedness needs to be realized through collaboration and participatory assistance.